A rare location of sacral tuberculosis: A report of three cases - Lazrak, Faiza (Eur J Rheumatol, 2014)
Tuberculosis remains one of the most common infectious diseases in the world. Vertebral tuberculosis is the commonest form of bone and joint tuberculosis; however, isolated sacral tuberculosis is rare. This atypical presentation may lead to a delay in diagnosis and treatment. We report three cases of sacral tuberculosis diagnosed in young women, aged 30, 23, and 35 years old, respectively. Lombosciatic pain was the main symptom in all cases. All patients had a biological assessment, plain radiographs, and CT scan. However, magnetic resonance imaging was done in only two cases. All patients underwent surgical sacral biopsy, and the diagnosis of tuberculosis was confirmed by histology in all cases. The evolution was satisfactory with the adjunction of antituberculous chemotherapy in all cases. Spinal tuberculosis should be the first and foremost differential diagnosis in the presence of atypical clinical and radiological features of a sacral lesion, particularly in developing countries. Early diagnosis and treatment could prevent or minimize the neurological morbidity in such cases.